A hybrid EDC/Flamelet approach for modelling biomass combustion of grate-firing furnace. Issue 4 (4th July 2019) - Farokhi, Mohammadreza; Birouk, Madjid
Abstract : This paper proposes a new combustion model for the simulation of biomass combustion. It is developed based on the framework of the well-known Eddy Dissipation Concept (EDC) approach, which has the ability to incorporate chemical kinetics in turbulent reacting flows and thus makes it suitable for modelling gas-phase combustion. However, its high computational cost when using detailed chemistry has made it impractical for modelling large/industrial setups. To address this handicap, the proposed approach decouples the real-time calculation of chemical and mixing processes by importing a pre-calculated steady laminar flamelet library into EDC. The development of this new model is performed based on a modified version of EDC (called Extended EDC), which is capable of modelling the gas-phase of biomass combustion over a wide range of turbulent flow conditions. The proposed model is validated by simulating the well-documented experiment of the piloted jet flames of Barlow and Frank. The performance of the model is then evaluated by simulating a small-scale grate firing biomass furnace. The results show that, overall, the proposed model can be used to model biomass combustion at substantially low computational cost.